1998
DOI: 10.1021/jp980355t
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Formation and General Phase Behavior in the Catanionic Mixture SDS−DDAB−Water. The Anionic-Rich Side

Abstract: Catanionic mixtures are aqueous mixtures of oppositely charged surfactants which display novel phase behavior and interfacial properties in comparison with those of the individual surfactants. One phase behavior property is the ability of these systems to spontaneously form stable vesicles at high dilution. The phase behavior of the mixture sodium dodecyl sulfate (SDS) -didodecyldimethylammonium bromide (DDAB) in water has been studied in detail, and two regions of isotropic vesicular phases (anionic-rich and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
271
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(301 citation statements)
references
References 46 publications
28
271
1
1
Order By: Relevance
“…At certain mixing ratios, lamellar structures form and a limited vesicular region can be found. 31 In the present study X SDS ) 0.71 was chosen; here small unilamellar vesicles (SUVs) are the dominant aggregates while multilamellar vesicles (MLVs) are sparsely detected. At this mixing ratio, vesicles are negatively charged and have a spherical shape with sizes in the range 20-70 nm, with an average size of 30 nm.…”
Section: Polycation-vesicle Complexes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…At certain mixing ratios, lamellar structures form and a limited vesicular region can be found. 31 In the present study X SDS ) 0.71 was chosen; here small unilamellar vesicles (SUVs) are the dominant aggregates while multilamellar vesicles (MLVs) are sparsely detected. At this mixing ratio, vesicles are negatively charged and have a spherical shape with sizes in the range 20-70 nm, with an average size of 30 nm.…”
Section: Polycation-vesicle Complexes Andmentioning
confidence: 99%
“…[29][30][31] It has also been shown that when an aqueous solution of such vesicles is mixed with an oppositely charged polymer, three different regions can be found 28,32 (I) A phase separation region, where a precipitate forms in equilibrium with a bluish solution. The phase separation is of the associative type, the precipitate being a coacervation complex of surfactant and polymer with a (near) zero net charge.…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have been investigating for some time vesicles in mixed cationic + anionic surfactant systems which form spontaneously, have an apparently unlimited life-time and are believed to be thermodynamically stable (21,35). The vesicles are polydisperse with sizes in the approximate range of 0.05 to 0.5 µm although there are also a few larger ones; the larger ones can be visualized directly by light microscopy while the smaller ones have been conveniently studied by cryogenic transmission electron microscopy (36,37). In our work we have introduced investigations of the interactions between these catanionic vesicles and DNA (38).…”
Section: Dna Is Compacted By Cationic Surfactantsmentioning
confidence: 99%
“…see reviews [10,11]). In this context, mixtures of oppositely charged surfactants have emerged in the last 10-15 years as an exciting new class of vesicle-forming systems (catanionic vesicles), as described further [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, results are also presented here for novel catanionic vesicles prepared from 12Lys12/DTAB [24] and 12Lys12/12Ser [25] mixtures. From a colloidal standpoint, catanionic vesicles bear several advantages as compared to conventional liposomes: (i) they form spontaneously upon mixing of individual co-solute micellar solutions, requiring no high-energy methods; (ii) they have long-term stability and in many cases exist as equilibrium structures (thus, indefinitely stable); (iii) they often present chain melting transitions well below room temperature; (iv) they offer the possibility of charge regulation, due to variation of the surfactant mixing ratio [9,[12][13][14][15]26,27].…”
Section: Introductionmentioning
confidence: 99%